Analyses on safety and efficacy of non-standard dose of r-tPA in intravenous thrombolysis-treated AIS patients - Yuan, Jiawen; Wu, Ruxing; Xiang, Jingyan; Deng, Jiangshan; Zhang, Xiaojie; Lu, Kaili; Cao, Fengya; Zhao, Fei; Zhao, Yuwu; Wang, Feng (Frontiers in Neurology, 2022)
Background Intravenous 0.9mg/kg recombinant tissue plasminogen activator (r-tPA) is one of the most effective treatments in acute ischemic stroke patients. Practically, the dose of r-tPA is still a topic that is constantly being discussed. Methods For this observational study, data was obtained from 537 patients who received r-tPA thrombolysis in Shanghai Sixth People’s Hospital stroke center over five years (2014-2019). Patients were divided into two groups: a nonstandard dose group (0.6mg/kg ≤ dose < 0.9mg/kg) and a standard dose group (0.9mg/kg). Different outcomes were observed: efficacy: 3 months mRS 0-1 (3m-mRS0-1); safety: symptomatic intracranial hemorrhage within 24 hours (24h-sICH) and 3 months mortality (3m-death). We also observed the effect of r-tPA dose coefficient on outcomes in different age groups and baseline National Institute of Health stroke scale (NIHSS) score subgroups. Results There were 265 patients given the standard dose treatment, and 272 given the nonstandard dose. There was no significant difference between the non-standard dose group and the standard dose group in 3m-mRS0-1, 3m-death and 24h-sICH (p=0.567, 0.327 and 0.415 respectively). The dose coefficient presents a significant negative correlation (p=0.034, B=-4.290) with 3m-death in NIHSS <16 sub-group. Door to needle time (DNT) is the most important independent outcome-influential factor (MIOIF) in the NIHSS ≥16 sub-group. The diabetes history and baseline NIHSS score were the MIOIF in the age ≥80-year sub-group. Conclusions The non-standard dose group (0.6mg/kg≤ dose <0.9mg/kg) shows no difference in safety and effectiveness than the standard dose group (0.9mg/kg) in our study. The Standard dose should be considered first according to current evidence and Guidelines, but the non-standard dose (0.6mg/kg≤ dose <0.9mg/kg) might be an option in the actual diagnosis and treatment process considering the patient’s clinical profile and financial condition.